The effect of concrete alkalinity on behavior of reinforcing polyester and polypropylene fibers with similar properties. (March 2019) - Rostami, Rouhollah; Zarrebini, Mohammad; Mandegari, Mansoor; Sanginabadi, Khaled; Mostofinejad, Davood; Abtahi, Sayyed Mahdi
Abstract: The use of fiber reinforced concrete (FRC) has received wide attention in recent years. Alkalinity affects polyethylene terephthalate (PET) fibers. Therefore, the use of PET fibers in an alkaline environment such as concrete is faced with uncertainties. In this work, three types of PET and polypropylene (PP) fibers with similar physical and mechanical properties were used as concrete reinforcement. In order to simulate the alkaline environment of concrete, hydrolysis of PET and PP fibers was carried out in 60 °C solution of NaOH 10% at pH = 14 for 1, 2, and 4 h duration. Fiber properties such as diameter, mechanical properties and moisture regain both before and after being subjected to alkaline hydrolysis were measured. Probable degradation of the fibers due to alkaline hydrolysis was evaluated using SEM and FTIR. The fibers were used in concrete at the same fiber volume fraction of 0.55%. FRCs were cured for 28 days and compressive, tensile and flexural strength were measured. Results showed that in initial stages of alkaline treatment severe weight loss of PET fibers occurred but beyond a certain time the rate of weight loss increased, slows down. Although mechanical properties of PET fibers in alkaline environment deteriorated due to weight reduction phenomenon, but results in generation of advantages such as hydrophilicity and creation of dimples on the surface of the treated fibers that enhanced adhesion properties of the fiber-matrix.